2005
DOI: 10.5897/ajb2005.000-3111
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the interaction of various oil types and rates on the mycelial wet and dry weights of Lentinus squarrosulus (Mont.) Singer and Psathyrella atroumbonata Pegler in submerged liquid cultures

Abstract: Lentinus squarrosulus and Psathyrella atroumbonata, two edible indigenous mushroom species, were cultured in various different media supplemented with coconut, cotton, groundnut, butterfat, palm kernel and palm oil respectively, at 5 different rates. The interaction of the various oil types with different rates produced highly significant differences (p<0.01) in the mean mycelial wet and dry weights. The heaviest mean wet and dry mycelial weight of L. squarrosulus was induced by butterfat x 0.007 ml/ml while f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…It has a good particle size that enables appropriate gas exchange. Moreover, its relatively high lipid content may stimulate mushroom growth (Wardle and Schisler 1969;Nwanze et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It has a good particle size that enables appropriate gas exchange. Moreover, its relatively high lipid content may stimulate mushroom growth (Wardle and Schisler 1969;Nwanze et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This may be attributed to the variations in their growth conditions since they were not cultivated in the same location. The works of Nwanze et al (2005aNwanze et al ( , 2005b on Lentinus squarrosulus and Psathyrella atroumbonata showed that both media composition and oil type influence the mycelial biomass of these mushrooms. Therefore, appreciable amount of extract and thus phenolic compounds and terpenoids can be recovered from P. ostreatus if its optimum growth condition is known.…”
Section: 1% (V/v) Tween-20mentioning
confidence: 99%
“…By maintaining the C/N ratio of 80:1 as obtained in the previous experiment (Table 5.0), the composition of carbon source was manipulated by combining sucrose with CPO, PKO and POME residues. Previous studies have reported on the utilization of several plant oils for the enhancement of mycelial growth and polysaccharides production [27,28,29,30]. To date, this is the first results reported on the stimulatory effect of palm oil and palm oil mill effluent (POME) residues for the enhancement of the mycelium biomass and the polysaccharide production by Pleurotus sp.…”
Section: Incorporation Of Cpo Pko and Pome Residues As Additional Camentioning
confidence: 89%
“…Based on the result obtained, additional of castor and olive oils have stimulated the cell growth of Schizophyllum commune and the concentration of 0.5% produced high EPS [28]. Previous research also reported that various different media supplemented with coconut, cotton, groundnut, butterfat, palm kernel and palm oil had significantly affect the mycelial growth of Psathyrella atroumbonata and Lentinus squarrosulus [27]. It is also stated that oil which has the function of an antifoam agent in fermentation has been favourable to mycelial growth in several medicinal mushrooms and to increase the production of bioactive metabolites [31,32,33].…”
Section: Effect Of Carbon To Nitrogen Ratio (C/n):-mentioning
confidence: 99%